Circular manufacturing 4.0: towards internet of things embedded closed-loop supply chains - Delpla, Victor; Kenné, Jean-Pierre; Hof, Lucas A. (International journal of advanced manufacturing technology, 2022)
Increased global economic competition and growing importance of environmental issues force manufacturers to consider implementation of closed-loop supply chains (CLSCs) ensuring recovery of end-of-life products (EOL) for recycling or reuse. Such CLSCs are subject to many uncertainties in their flows given the varying conditions of EOL products. In the era of Industry 4.0, developments in the field of the internet of things (IoT) allow the collection of data throughout full product life cycles to determine most optimal treatments to apply after product recovery. This study proposes a CLSC model maximizing the total profit of the manufacturing company by selecting the treatment to be applied to the collected products according to their condition as estimated by life cycle data collection enabled by IoT. A mixed integer linear programming model is considered for a modular product sharing standard components. To validate the proposed CLSC model on an actual innovative real-world application, we used a modular smartphone as case study. The developed model proposes a solution for the return loop of a CLSC to meet a refurbished product demand over multiple periods. The interest of using intelligent devices that predict the degradation of products during their life cycle is highlighted. The full implementation of such intelligent tracking technology on all products, and not only partially, would be beneficial by more than 5.3% for high remanufacturing costs. The profit would increase by more than 49% if the quantity of recoverable EOL products exceeded the demand for refurbished products.